Electro-deposition of coating of dental implant - Prathama, Clinton (2019)
This report presents the processes, techniques and methods utilized in developing an optimized antimicrobial coating for Titanium dental implants. Titanium foils were used instead of Titanium implant because of geometry and ease of analysis and preparation considerations. All coated Ti foils were deposited with 1%w/v pyrogallol and different concentration of Linear Polyethyleneimine, ε-Poly L-lysine, and AgNO3. Antimicrobial activity of coated foils was tested against bacteria such as Escherichia coli and Staphylococcus aureus. The anti-microbial coating was applied using electrophoretic deposition technique with Platinum cathode and Ti foils as the anode. While current was kept constant at 0.06 A, voltage and duration of deposition were varied. Results showed that Ti foils coated with Pyrogallol and AgNO3 gave highest antimicrobial activity with very low CFU/ml obtained. Against Escherichia coli, as LPEI, EPL, and AgNO3 concentration increased the antimicrobial activity also increased shown by decreased in CFU/ml in the plotted graph of log of CFU/ml. Coated Ti foils were analysed for three characterisation techniques specifically Fourier Transform Infrared, Water Contact Angle, Atomic Force Microscopy and Secondary Electron Microscopy. FTIR results showed that PG, LPEI, and EPL were successfully deposited into Ti foils. Water contact angle results revealed difficulty in analysis due to uneven surface and coating on TI foils. Under 2000x magnification of SEM, coatings formed on Ti foils were continuous layer and strongly adhered. For AgNO3 presence in Ti foils, FTIR results only showed presence of NO2 group in the fingerprint region rendering the analysis to be indecisive. Thus, Energy Dispersive X-ray analysis were carried out for samples deposited with AgNO3. Under AFM analysis, surface found to be very rough due to substrate (Ti foils) undergone autopolishing to remove passivation layer protecting the Ti layer beneath from corrosion.